The creation of the world, from Armenian Paulicianism to Bulgarian Bogomilism and Western Catharism (Colloquia Comparativa Litterarum, 2025)
According to a Cathar legend retold in 1960 in the tale The Santa Estela del Centenari (The Holy Estella of the Centennial, written by Occitan and French author Joan Bodon or Jean Boudou, Satanael or Satan, the evil demiurge, had created the world. This account of the origins is also the story of the Bogomils in Bulgaria. The belief originated in Armenia, on the border between the Persian Sasanian Empire and the Eastern Roman Empire, between the 5th and the 7th centuries A.D. Since the end of the 19th century, however, these conceptions have resurfaced again in modern literature, theatre, novels, and poetry, both in Bulgaria and in France. What can a comparativist literary approach based on the scarce Cathar, Bogomil, and Paulician texts we have at our disposal reveal about this lost account of the origins of the world, and about the questions posed by Paulicians, Bogomils and Cathars on the existence of God, evil, and man?
Keywords: cosmogony; heresy; Catharism; Bogomilism; Paulicianism; Zoroastrianism; Mazdeism; literature; literature; moral